2013
DOI: 10.4149/neo_2013_066
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-217, down-regulated in clear cell renal cell carcinoma and associated with lower survival, suppresses cell proliferation and migration

Abstract: Aberrantly expressed microRNAs (miRNAs) are frequently correlated with a variety of human cancers, including clear cell renal cell carcinoma (ccRCC). In this study, we determined the expression patterns of miR-217 in ccRCC, and tested its effect on cancer cell proliferation and migration. The expression levels of miR-217 were determined in 54 ccRCC samples using Real-Time qPCR. 786-O and ACHN cells were transfected with miR-217 mimics or miRNA mimics control. Cell proliferation and migration were evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 14 publications
4
38
1
2
Order By: Relevance
“…Our results are consistent with the notion that these miRNAs regulate numerous genes that promote tumor progression and which may be expressed differentially in different metastatic tumors. Notably, miR-216b and miR-217 have previously been implicated as inhibitors of tumor growth and invasion in nasopharyngeal, renal clear cell, and pancreatic ductal carcinoma (Deng et al 2011;Ali et al 2012;Li et al 2013b). Further, each member of the Mir216/ 217 cluster was demonstrated to possess a significant cis-acting eQTL, indicating that differences in Mir216/217 expression across the AKXD RI panel are inherited and not acquired somatically during neoplastic transformation or tumor progression.…”
Section: Discussionmentioning
confidence: 93%
“…Our results are consistent with the notion that these miRNAs regulate numerous genes that promote tumor progression and which may be expressed differentially in different metastatic tumors. Notably, miR-216b and miR-217 have previously been implicated as inhibitors of tumor growth and invasion in nasopharyngeal, renal clear cell, and pancreatic ductal carcinoma (Deng et al 2011;Ali et al 2012;Li et al 2013b). Further, each member of the Mir216/ 217 cluster was demonstrated to possess a significant cis-acting eQTL, indicating that differences in Mir216/217 expression across the AKXD RI panel are inherited and not acquired somatically during neoplastic transformation or tumor progression.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, miR-375 is associated with drug resistance in ovarian (71) and cervical cancer (72). Although no study has reported the role of miR-32 and -217 in drug resistance, it is associated with drug resistance-related processes such as cell proliferation, invasion and migration (73)(74)(75). Collectively, among the 7 microRNAs most strongly targeting HNF1B, the majority were involved in drug resistance in ovarian and other types of cancers, suggesting that the gene also mediates drug resistance.…”
Section: Microrna-mrna Interaction Analysis Indicating the Associatiomentioning
confidence: 99%
“…In hepatocellular carcinoma, endogenous miR-217 expression inhibited cell invasion by directly targeting E2F transcription factor 3 (26). In clear cell renal cell carcinoma, ectopic expression of miR-217 suppressed cell proliferation, migration and invasion (27). These studies indicate that miR-217 mainly functions as a tumor suppressor in several types of cancer.…”
Section: Discussionmentioning
confidence: 75%
“…The low expression level of miR-217 was notably correlated with tumor differentiation and shorter overall survival for patients with colorectal cancer (24). Additionally, miR-217 was found to be downregulated in lung (25), hepatocellular (26) and clear cell renal cell carcinoma (27) and pancreatic ductal adenocarcinoma (28). However, in breast cancer, miR-217 was upregulated in tumor tissues in comparison with normal breast tissues.…”
Section: Discussionmentioning
confidence: 84%